Interpretasi Tafsir Ekologi Dan Hakikat Kepemimpinan: Telaah QS. Ar-Rum : 41 menggunakan teori Maqashidu Syari’ah - Muhammad Farhan Akbar; M. Yunan Yusuf (CV. Creative Tugu Pena, 2024)
The rise of the issue of environmental damage has become a global problem of concern, most of the causes come from human actions themselves. This study aims to examine the interpretation of Qs. Ar-Rum: 41 which explains the destruction of